ANALISIS RENCANA ANGGARAN BIAYA PADA PROYEK PENINGKATAN SALURAN SEKUNDER IRIGASI ALEBBONG KABUPATEN SIDENRENG RAPPANG - Muh Yusuf Mubarak; Sulfanita, Andi; Didi, Andi Bustan; Muhammadiah, Muh Jabir (Jurnal Teknik Sipil dan Arsitektur, 2026)
This study discusses the importance of managing the cost budget in construction projects that must be planned efficiently and effectively, so that project implementation can meet the main requirements, namely cost, time, and quality. The Alebbong Irrigation Area has an area of 20 Ha, but often experiences damage such as landslides so that channel repair and rehabilitation are required. This research method uses a RAB calculation analysis that refers to the need for secondary channel work and complementary buildings at the project site. The data used includes labor requirements, wages, and material costs calculated based on applicable standards. The results of the study show that the total RAB for the work is Rp 457,757,860.26 consisting of channel work and Tapping I and II work with a total volume of 2,675.503 m^3 which is rehabilitated. From this study, the cost budget plan is quite significant between the results of the RAB calculation analysis of previous studies. Therefore, it is recommended that before conducting the RAB analysis, complete data and more detailed planning drawings are needed so that the cost estimation results are more accurate.